INTEGRATED APPROACH TO IMPROVE CONSUMER PROPERTIES OF FERTILIZERS ON THE EXAMPLE OF CALCIUM SALTPETRE - Дмитриков, В. П.; Шестозуб, А. Б.; Олійник, М. А. (Scientific Progress & Innovations, 2015)
The last researches and publications the decision of problem is grounded in which are analysed. Possibilities of the complex approach to the increase of consumer demand of agricultural enterprises on calcium saltpetre are presented. Measures of the improvement of technology of calcium saltpetre production are offered. The calculation of charges of raw material and energy of production of solutions of calcium saltpetre is performed with neutralizing addition potassium of carbonate. The measures of modification lead cutting of power costs, upgrading of calcium saltpetre, improvement of ecological indexes of production.